IMPLEMENTASI KEBIJAKAN PERSETUJUAN BANGUNAN GEDUNG OLEHDINAS PEKERJAAN UMUM DAN PENATAAN RUANG DI KABUPATENPURBALINGGA - Monita Rahayuningtyas; Esti Ningrum; Haris Kusumawardana; Wahyu Hariadi (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2023)
Since the enactment of Law Number 11 of 2020 concerning Job Creation which has now been replaced by LawNumber 6 of 2023 concerning the Stipulation of Government Regulation in lieu of Law Number 2 of 2022 concerningJob Creation to Become a Law, the government removed the term Building Permit (IMB) was replaced with aBuilding Approval (PBG) as one of the conditions for constructing a building. PBG is a permit granted to buildingowners to build new, change, expand, reduce, and/ or maintain buildings in accordance with building technicalstandards (Article 1 Number 17 Government Regulation Number 16 of 2021 concerning Implementing Regulationsof Law Number 28 2002 concerning Building Buildings). This study aims to analyze the implementation of theBuilding Approval (PBG) policy based on the Regional Regulation of Purbalingga Regency Number 3 of 2022concerning Retribution for Building Approvals and the obstacles in granting PBG by the Public Works and SpatialPlanning Office in Purbalingga Regency. The research method uses a normative juridical approach and data analysisin this study uses qualitative analysis. Data collection techniques were carried out by reviewing laws and regulationsrelated to buildings and conducting interviews as supporting or additional data. The results of this study indicatethat in the provision of PBG by the DPU-PR Purbalingga there are still obstacles that affect the course of the policy,including the lack of public awareness of the importance of obtaining PBG, a lack of understanding of PBGprocedures and requirements through SIMBG, and a lack of professional planners at the DPU-PR of the RegencyPurbalingga.